Optimización del sistema de explotación del área minera “El Diamante” código 600841 barrio “El Huayco”, cantón Catamayo, provincia de Loja - Martínez Maldonado, Karen Paola (2023)
The present research degree work proposes "Optimize the exploitation system of the mining area "El Diamante" code 600841 "El Huayco" neighborhood, Catamayo canton, Loja province " with the purpose of avoiding damage to the banks of the Catamayo River that affects the “La Sota” drinking water collection located 7 km away, for which, by collecting field information and interviews, an analysis of the current situation was carried out, describing the productive activities in the mining area that is not currently in production. , in this way it was collected and processed, obtaining data of interest necessary for the development of this research. In the first instance, the geology, topography, climate, temperature, precipitation, and hydrology were determined as base data in the area. In addition, reserve calculations were carried out, material drag calculation by the Catamayo River based on the climatic conditions, performance of the machinery. , production rate, life time of the gravel pit, production costs per m3 of material, analysis of the quality of the material that allows determining its uses. The survey and studies of data obtained from the mining area allow the understanding of the behavior of the sector when it was exploiting, verifying the inefficiency of the performance of the machinery and the technical and environmental need for the construction of transverse dams for which the design is proposed. Analyzing the results obtained, they improve daily production and reduce the production cost, demonstrating the viability of what was proposed in the study.. Keywords: open pit, gravel pits, cross dikes, gabions, design, scour